Engineering a mobile platform to promote sleep in the pediatric primary care setting. Issue 1 (15th April 2021) - Mitchell, Jonathan A; Morales, Knashawn H; Williamson, Ariel A; Huffnagle, Nicholas; Eck, Casey; Jawahar, Abigail; Juste, Lionola; Fiks, Alexander G; Zemel, Babette S; Dinges, David F
Abstract: Study Objectives: Pediatricians lack tools to support families at home for the promotion of childhood sleep. We are using the Multiphase Optimization Strategy (MOST) framework to guide the development of a mobile health platform for childhood sleep promotion. The objective of this study is to demonstrate feasibility of a mobile health platform towards treating children with insufficient sleep. Methods: Children aged 10–12 years were enrolled (Study #1: N = 30; Study #2: N = 43). Participants wore a sleep tracker to measure sleep duration. Data were retrieved by a mobile health platform, programmed to send introductory messages during run-in (2 weeks) and goal achievement messages during intervention (7 weeks) periods. In study #1, participants were randomized to control, gain-framed incentive or loss-framed incentive arms. In study #2, participants were randomized to control, loss-framed incentive, normative feedback or loss-framed incentive plus normative feedback arms. Results: In study #1, 1514 nights of data were captured (69%) and sleep duration during the intervention was higher by an average of 21 (95% CI: −8, 51) and 34 (95% CI: 7, 61) minutes per night for the gain-framed and loss-framed arms, respectively, compared to controls. In study #2, 2, 689 nights of data were captured (81%), with no major differences in average sleep duration between the control and the loss-framed or normative feedback arms. Conclusions: We have developed and deployed a mobile health platform that can capture sleep data and remotely communicate with families. Promising candidate intervention components will be further investigated under the optimization phase of the MOST framework. Clinical Trials: Both studies included in this manuscript were registered at clinicaltrials.gov: -Study #1: NCT03263338 -Study #2: NCT03426644